3 Epidemiology of Intractable Epilepsy in Children (Pediatric Epilepsy Surgery, 2019)
The epidemiology of intractable epilepsy in children is complex but potentially important in choosing candidates for epilepsy surgery. The overall incidence of epilepsy in children is estimated to be from about 30 to 80 cases per 100,000 persons per year, and it is highest in the first year of life. Between ages 11 to 15 years the incidence is similar to adults. The prevalence is higher (about 3–6/1,000). Intractable, pharmacoresistant and resistant epilepsy have varying definitions in the published literature with the risk being between approximately 8 and 20% of children with epilepsy. About one-third or more of children with intractable epilepsy will eventually have a lengthy or permanent remission of their seizures, although others may have periods of seizure control mixed with periods of resistant epilepsy. Accurate prediction of the outcome of intractability is currently impossible. It is statistically associated neurological deficits, intellectual disability, early high seizure frequency, a few epilepsy syndromes, temporal lobe epilepsy, and causative lesions on MRI. Importantly, about one-third of children with epilepsy and an MRI identified cause will still have remission. It is unclear if intractable epilepsy in children is associated with sudden unexpected deaths in epilepsy (SUDEP) even if epilepsy persists into adulthood.
Keywords: epidemiology; intractable; epilepsy; children; outcome